Request a call back

Join NOW to get access to exclusive study material for best results

CBSE Class 10 Answered

Page 231 If the pth term of an AP is q and the qth term is p, then prove that its nth term is (p+1-n) and hence prove that its(p+q)th term is zero.
Asked by miniprasad | 08 Dec, 2018, 10:42: PM
answered-by-expert Expert Answer
Let a is the first term of AP and d is the common difference
pth term = a + (p-1) d = q .................(1)
qth term = a + (q-1) d = p .................(2)
 
By subtracting eqn(2) from eqn(1), we get d = -1
 
if we subsititue d = -1 in eqn.(1), we get a = p+q-1
 
nth term = a+(n-1)d = (p+q-1) + (n-1)(-1) = p+q-n
 
(p+q)th term = a+(p+q-1)d = (p+q-1)+(p+q-1)(-1) = 0
Answered by Thiyagarajan K | 09 Dec, 2018, 12:35: AM
CBSE 10 - Maths
Asked by rrajansinghakb199 | 08 Apr, 2024, 05:12: PM
ANSWERED BY EXPERT ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by nagalaxmidurgarao937 | 08 Apr, 2024, 01:42: PM
ANSWERED BY EXPERT ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by sonawnerohan01 | 23 Mar, 2024, 12:25: PM
ANSWERED BY EXPERT ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by pathakvaishnavi9139 | 23 Mar, 2024, 10:45: AM
ANSWERED BY EXPERT ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by choudharyniki001 | 22 Mar, 2024, 08:49: AM
ANSWERED BY EXPERT ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by vn3950372 | 18 Mar, 2024, 08:38: PM
ANSWERED BY EXPERT ANSWERED BY EXPERT
Get Latest Study Material for Academic year 24-25 Click here
×